A phase 2 trial of gemcitabine and docetaxel in patients with metastatic colorectal adenocarcinoma with methylated checkpoint with forkhead and ring finger domain promoter and/or microsatellite instability phenotype. Issue 3 (3rd April 2021) - Baretti, Marina; Karunasena, Enusha; Zahurak, Marianna; Walker, Rosalind; Zhao, Yang; Pisanic, Thomas R.; Wang, Tza‐Huei; Greten, Tim F.; Duffy, Austin G.; Gootjes, Elske; Meijer, Gerrit; Verheul, Henk M.W.; et al.
Abstract : Abstract: We previously reported CHFR methylation in a subset of colorectal cancer (CRC; ∼30%) with high concordance with microsatellite instability (MSI). We also showed that CHF R methylation predicted for sensitivity to docetaxel, whereas the MSI‐high phenotypes were sensitive to gemcitabine. We hypothesized that this subset of patients with CRC would be selectively sensitive to gemcitabine and docetaxel. We enrolled a Phase 2 trial of gemcitabine and docetaxel in patients with MSI‐high and/or CHFR methylated CRC. The primary objective was Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 response rate. Enrolled patients were treated with gemcitabine 800 mg/m 2 on days 1 and 8 and docetaxel 70 mg/m 2 on day 8 of each 21‐day cycle. A total of 6 patients with CHFR ‐methylated, MSI‐high CRC were enrolled from September 2012 to August 2016. The study was closed in September of 2017 due to poor accrual prior to reaching the first interim assessment of response rate, which would have occurred at 10 patients. No RECIST criteria tumor responses were observed, with 3 patients (50%) having stable disease as best response, 1 lasting more than 9 months. Median progression‐free survival (PFS) was 1.79 months (95% confidence interval [CI] = 1.28, not available [NA]) and median overall survival (OS) was 15.67 months (95% CI = 4.24, NA). Common grade 3 toxicities were lymphopenia (67%), leukopenia (33%), and anemia (33%). Although negative, this study establishes a proof‐of‐concept for the implementation of epigenetic biomarkers ( CHFR methylation/MSI) as inclusion criteria in a prospective clinical trial to optimize combinatorial strategies in the era of personalized medicine. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? CHFR silencing via DNA methylation has been suggested to be predictive of taxane sensitivity in diverse tumors. The frequent association of CHFR methylation with microsatellite instability (MSI) suggested a possible combination therapy with gemcitabine, because the MSI phenotype may result in sensitivity to nucleoside analogues. WHAT QUESTION DID THIS STUDY ADDRESS? We hypothesized that metastatic colorectal cancer (mCRC), which have CHFR methylation and MSI phenotype were sensitive to gemcitabine and docetaxel, and have designed this Phase 2 trial in biomarker‐selected mCRC to test this prediction. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? The study enrolled a molecularly defined subgroup of patients with colorectal cancer (CRC) and showed that the combination is safe in this population. Nevertheless, due to poor enrollment and early termination, no conclusions on the primary and secondary end points could be made. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? This study supports the feasibility of implementing DNA methylation markers in a prospective clinical trial and further efforts toward their application as predictive biomarkers for therapeutic agents in defined subsets of patients are warranted.